2021
DOI: 10.1002/fsn3.2160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficit on leaves and fruit quality during the development period in tomato plant

Abstract: In nature, plants are often exposed to a multitude of environmental constraints that severely limit crop productivity. Water deficit is one of the factors that most affects agricultural production. The aim of this work is to evaluate the effect of water deficit on morphology, development, nutritional behavior, as well as chlorophyll fluorescence and certain important metabolic parameters (soluble sugars, organic acids, starch, carotenoid, and vitamin C) of the cultivated tomato (Solanum lycopersicum cv Plovdiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 53 publications
5
23
0
1
Order By: Relevance
“…While N reduction delayed fruit maturation in most cultivars and at both locations, water deficit had the opposite effect. Previous studies highlighted a shortened ripening period when water stress is applied, reporting an increase in vitamin C and carotenoids when the deficit is applied during the maturation stage ( Ripoll et al, 2016 ; Medyouni et al, 2021 ). In addition, it has been observed that low N content delays fruit development, reducing furthermore the content of sugars, thus impacting negatively the overall quality ( Khan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…While N reduction delayed fruit maturation in most cultivars and at both locations, water deficit had the opposite effect. Previous studies highlighted a shortened ripening period when water stress is applied, reporting an increase in vitamin C and carotenoids when the deficit is applied during the maturation stage ( Ripoll et al, 2016 ; Medyouni et al, 2021 ). In addition, it has been observed that low N content delays fruit development, reducing furthermore the content of sugars, thus impacting negatively the overall quality ( Khan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cape gooseberry fruits, citric acid constitutes 85% of the organic acids (Novoa et al, 2006). Medyouni et al (2021) reported that, when tomato plants suffered water stress, they reduced water absorption and increased the production of acids in the fruits as a mechanism of adaptation to stress, where ascorbic acid and total carotenoids stand out. A similar result was found for the cape gooseberries in this study and in another study on the tomato (Patané et al, 2011).…”
Section: Total Titratable Acidity (Tta)mentioning
confidence: 99%
“…Otro factor externo que influye en la relación y la fuerza de los órganos fuente/vertedero, y en la distribución de los fotoasimilados, es el déficit hídrico del suelo, el cual, promueve un estrés de tipo abiótico en las plantas (Rodrigues et al, 2019). El estrés hídrico en las plantas ha sido asociado como uno de los factores ambientales que afecta los rendimientos y el desempeño fisiológico de los cultivos de tomate (Chen et al, 2013;Medyouni et al, 2021;Luo et al, 2021). Una de las respuestas fisiológicas que afecta el estrés hídrico en las plantas es el cierre de las estomas, lo cual, limita la asimilación de CO 2 , disminuye la tasa de carboxilación, la producción de fotoasimilados y en general afecta la relación de órganos fuente/vertedero (Sun et al, 2020).…”
Section: Condiciones De Estrés Hídricounclassified